If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -3 = 5 Reorder the terms: -3 + -2x = 5 Solving -3 + -2x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 5 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 5 + 3 -2x = 5 + 3 Combine like terms: 5 + 3 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| -1-x=-2(6x+6) | | g(x)=x^3-3x^2-4x+12 | | 4y+y^2-247=0 | | 4(2x-3)+3=15 | | 24x-5-13x+3=21x-9-10x+12 | | 2(2x+1)=2x+8+x | | X^2+9y^2-36y+27=0 | | x^2+22x=416 | | 5x-6=4.5x-2 | | 3x+7-3=10x+2x-4 | | 7x+5+19=180 | | ln(4)+ln(x)=0 | | x+(x+5)+(x+11)=55 | | 2y=3(3y-5) | | 1=7/8y=4.5 | | 4x+12-9x=17-17x+12x-5 | | 2x+(1+x)3=4(x-1) | | 4*x=y/3 | | 6x-3y=20+8y | | 11=(q) | | x-2=-9x+108 | | 2+5=-3x | | (m)=3 | | 2z-1=80 | | -4/14 | | 3y+5.2=2.5 | | 5y-8y=-5 | | 20+16+10=180 | | 0=-7x+4-5x | | S+9=19 | | 4t+9+(2t+7)+6= | | 20+16+10= |